2020
DOI: 10.1136/oemed-2020-106519
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to whole-body vibrations and pregnancy complications: a nationwide cohort study in Sweden

Abstract: ObjectivesPregnancy complications are common contributors to perinatal mortality and morbidity. Still, the cause(s) of gestational hypertensive disorders and diabetes are largely unknown. Some occupational exposures have been inconsistently associated with pregnancy complications, but exposure to whole-body vibrations (WBV) has been largely overlooked even though it has been associated with adverse birth outcomes. Therefore, the aim was to assess whether occupational WBV exposure during pregnancy is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…As noise exposures in occupational settings are very different in their features, further research is necessary to define a possible dose-response relationship, specific molecular mechanisms of action and to deeply investigate the complex interplay between noise characteristics, in terms of i.e., type, intensity and duration of exposure, and individual characteristics of women, i.e., age of the pregnant women, anthropometric parameters and pregnancy periods of exposure, as well as collective and individual protective measures adopted in the workplace in influencing HDP onset [49,51]. No sufficient information is currently available on the role of extreme temperature and vibration exposure in determining HDP, with only one study showing a statistical association between exposure to WBV and the risk of HDP [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noise exposures in occupational settings are very different in their features, further research is necessary to define a possible dose-response relationship, specific molecular mechanisms of action and to deeply investigate the complex interplay between noise characteristics, in terms of i.e., type, intensity and duration of exposure, and individual characteristics of women, i.e., age of the pregnant women, anthropometric parameters and pregnancy periods of exposure, as well as collective and individual protective measures adopted in the workplace in influencing HDP onset [49,51]. No sufficient information is currently available on the role of extreme temperature and vibration exposure in determining HDP, with only one study showing a statistical association between exposure to WBV and the risk of HDP [53].…”
Section: Discussionmentioning
confidence: 99%
“…Haelterman et al [35] and Irwin et al [47] showed no association between extreme temperatures and HDP. Only two studies analyzed the association between exposure to WBV and HDP risk in women [35,53]. Haelterman et al [35] found that WBV slightly raised, although not significantly, the risk of PE (aOR 1.2).…”
Section: Physical Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, although over the last decades female participation in the workforce has risen, work-related risks to women’s health are less studied. 13 For instance, even studies of occupational risks for pregnant women have focused on fetal effects for decades, but recent studies also suggest an increased risk of pregnancy-related health effects in women exposed to physical risk factors like noise and vibration. 14,15 Lastly, insights into informative biological pathways and biomarkers to link exposure to health are mostly lacking.…”
Section: Introductionmentioning
confidence: 99%
“… 13 For instance, even studies of occupational risks for pregnant women have focused on fetal effects for decades, but recent studies also suggest an increased risk of pregnancy-related health effects in women exposed to physical risk factors like noise and vibration. 14 , 15 Lastly, insights into informative biological pathways and biomarkers to link exposure to health are mostly lacking. These could contribute to the quantitative understanding of exposure-response associations and provide agnostic discovery of biomarkers for exposure monitoring.…”
Section: Introductionmentioning
confidence: 99%